5‐Florouracil‐loaded poly(lactic acid)‐poly(caprolactone) hybrid scaffold: Potential chemotherapeutic implant. Issue 8 (3rd September 2013) - Gupta, Kamal K.; Pal, Namrata; Mishra, Pradeep K.; Srivastava, Pradeep; Mohanty, Sujata; Maiti, Pralay
Abstract Hybrid nanofibers of poly(lactic acid) and polycaprolactone have been developed by embedding cancerous drug through electrospinning technique. The composition of polymer has been varied to check the compositional effect on properties. The quality of nanofibers has been testified through surface morphology, wetting properties using contact angle and mechanical strength under uniaxial elongation. The compatibility of drug (5‐fluorourasil) with matrix fiber has been verified using Fourier transform infrared, X‐ray diffraction, Raman spectroscopy, and differential scanning calorimetry. The drug release study has been performed showing greater release in hybrid fibers when compared with pure polymers as a result of synergism of two immiscible polymers and quasi‐Fickian diffusion mechanism in hybrid nanofiber as implants showing compositional effect on drug release. A model has been proposed showing faster release of drugs in hybrid systems. Biological responses through fluorescence imaging and MTT assay confirm the release of drug from hybrid nanofibers showing potential use of hybrid scaffolds as chemotherapeutic implant. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 2600–2612, 2014.